Mechanisms of Oxygen Vacancy Aggregation in SiO2 and HfO2 - Gao, David Z.; Strand, Jack; Munde, Manveer S.; Shluger, Alexander L. (Frontiers in Physics, 2019)
Dielectric oxide films in electronic devices undergo significant structural changes during device operation under bias. These changes are usually attributed to aggregation of oxygen vacancies resulting in formation of oxygen depleted regions and conductive filaments. However, neutral oxygen vacancies have high diffusion barriers in ionic oxides and their interaction and propensity for aggregation are still poorly understood. In this paper we briefly review the existing data on static configurations of neutral dimers and trimers of oxygen vacancies in technologically relevant SiO2 and HfO2 and then provide new results on the structure and properties of these defects in amorphous SiO2 and HfO2. These results demonstrate weak interaction between neutral O vacancies, which does not explain their quick aggregation. We propose that trapping of electrons, injected from an electrode, by the vacancies may result in creation of new neutral vacancies in the vicinity of pre-existing vacancies. We describe this mechanism in a-SiO2 and demonstrate that this process becomes more efficient as the vacancy clusters grow larger.